THE INFLUENCE OF MULTIPLE ROLES AND WORK MOTIVATION ON THE PERFORMANCE OF FEMALE EMPLOYEES IN THE EDUCATION OFFICE NORTH LABUHANBATU DISTRICT - Elda Anzeli Hasibuan; Nurbaiti Nurbaiti; M Ihsan Harahap (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2023)
The purpose of this study was to determine the effect of dual roles and work motivation on the performance of female employees at the North Labuhan Batu Regency Education Office. This type of research is explanatory research, with data collection techniques through questionnaires. The sampling technique used purposive sampling technique. The sample amounted to 20 respondents who were female employees of the North Labuhan Batu Regency Education Office. This research uses quantitative analysis techniques. Quantitative analysis using the correlation coefficient test, the coefficient of determination, significant tests (t test and F test). The results of this study indicate that the effect of dual roles (X1 ) on employee performance (Y) from the analysis obtained that the significant value of 0.000 <0.05 so it can be concluded that there is a significant influence between dual roles on employee performance. The effect of work motivation (X2 ) on employee performance (Y) from the analysis obtained that a significant value of 0.000 <0.05 so it can be concluded that there is a significant influence between work motivation on employee performance.